ANALISIS NILAI MORAL PADA CERPEN “MISTERI UANG MELAYANG” KARYA SONA - Pahruroji Pahruroji; Fajar Julianto; Riana Dwi Lestari (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The short story "Misteri Uang Melayang" is one of the literary works that can be used as motivation for readers and writers. The contents of this short story are very interesting because the contents of the story are common in everyday life. Various moral polemics in aspects of life are manifested clearly by the authors, especially those that occur in the world of education. The problem statement focuses on moral values. The purpose of his research was to analyze the moral values contained in Sona's short story entitled “Misteri Uang Melayang”. This research uses a qualitative descriptive method. Data collection in this research by reading, analyzing, and marking texts or sentences that are included in moral values. This is done so that moral values in the short story are easily identified and implemented in daily life by the reader. Through this research, the reader is expected to be able to reap the moral values presented by the author in his short story. Through the research, the moral values in this story never give up, willing to sacrifice and without ulterior motives, hard work, creative, forgive each other and don’t be cunning and cheating to get things done. Through the research process, the author seeks to integrate moral values well so that the desired goals can reach the reader. Thus it can be concluded that the short story produced by Sona is suitable to be read by all groups, both ordinary people and intellectuals. Teenagers and parents can enjoy it too.